2020
DOI: 10.1080/17461391.2020.1739143
|View full text |Cite
|
Sign up to set email alerts
|

Attention, working‐memory control, working‐memory capacity, and sport performance: The moderating role of athletic expertise

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 50 publications
0
44
1
Order By: Relevance
“…Taking into account the limitations of conventional performance tests, recent research has sought to identify alternatives supplementing the current diagnostic spectrum. A plethora of studies focused on the potential role of perceptual-cognitive function [ 5 , 6 , 7 , 8 , 9 , 10 ]. Briefly, it has been suggested that superior levels of related skills (e.g., visual scanning, attention, working memory, inhibitory control) could help to increase sports performance and prevent injury [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the limitations of conventional performance tests, recent research has sought to identify alternatives supplementing the current diagnostic spectrum. A plethora of studies focused on the potential role of perceptual-cognitive function [ 5 , 6 , 7 , 8 , 9 , 10 ]. Briefly, it has been suggested that superior levels of related skills (e.g., visual scanning, attention, working memory, inhibitory control) could help to increase sports performance and prevent injury [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a review of 91 studies on athletic expertise, Swann et al (2015) concluded that a final consensus is difficult to reach because of heterogeneity in the ways past investigators classified athletic expertise. Swann et al (2015) proposed a standardized taxonomy across sport type accommodating the highest level of performance in terms of success, experience, the competitiveness of the sport, and the global representativeness of the sport; this proposal has received support from others (Hagyard et al, 2021;Vaughan & Laborde, 2020).…”
Section: The Present Studymentioning
confidence: 99%
“…Inconsistencies in this literature may be explained by methodological differences between studies, including (a) variations in the tasks that were used to measure EF, (b) failing to capture EF complexity by using only single outcome measures of efficiency or effectiveness, and/or (c) investigators’ use of different taxonomies to portray athlete expertise ( Furley & Wood, 2016 ; Jacobson & Matthaeus, 2014 ; Swann et al., 2015 ; Vaughan & Edwards, 2020 ). Recent, research has shown that EF may interact with other processes to best explain sport performance ( Vaughan & Laborde, 2020 ). Considering the respective importance of both mood and EF for athletes of differing expertise levels, these two factors are likely to interact in their influence on performance.…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, it has been suggested that individuals who achieve high levels of expertise also show enhanced performance across a wide range of core cognitive or perceptual domains in general, outside the specific context of their expertise. To continue with the example of sports, several recent studies have found that elite athletes outperform non-athletes in cognitive tests evaluating attention, multitasking, working memory, and processing speed, with group effects ranging from small to medium effect sizes (Faubert, 2013;Scharfen & Memmert, 2019;Vaughan & Laborde, 2020;Voss et al, 2010). Professional athletes also showed faster improvement in performance on a three-dimensional multipleobject-tracking task (3D-MOT) as a function of training, compared to high-level amateurs and to non-athletes (Faubert, 2013;Faubert & Sidebottom, 2012).…”
Section: Introductionmentioning
confidence: 99%